Growth of spray pyrolysis deposited copper oxide thin film - Dhawankar, Sachin; Patil, Avish; Suryavanshi, Bhagwat; Tripude, Manish (International Journal of Physical Research, 2016)
Copper oxide thin film is deposited on the glass slide using aqueous solution of copper chloride and hydrogen peroxide by using spray pyrolysis deposition technique. The deposited CuO thin film is adherence and homogeneity with high transparency in visible region. Investigation of CuO thin film for physical properties is done. By using UV –Visible Spectrophotometer optical properties like absorption, transmission, energy band gap, Absorption coefficient and extinction coefficient in the visible region (380 – 1000 nm) are studied. The X-ray diffraction of CuO thin film is polycrystalline in nature with monoclinic crystal structure. The resistivity of Cuo thin film is studied using four probe methods.